Methods of the National Collegiate Athletic Association injury surveillance program, 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; Wasserman, E. B.; Boltz, A. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Background: Since 1982, the National Collegiate Athletic Association (NCAA) has collaborated with athletic trainers (ATs) to create the largest ongoing collegiate sports injury database in the world. This report provides an operational update of the NCAA Injury Surveillance Program (NCAA ISP) during the academic years 2014-2015 through 2018-2019. Surveillance system structure The NCAA ISP used a convenience sampling technique via a rolling recruitment model. The ATs at contributing institutions voluntarily submitted data into their respective electronic medical record systems; common data elements were pushed to and maintained by the Datalys Center. The ATs provided information about all team-related activities, even if no injury occurred during that activity, as well as detailed reports on each injury, including condition and circumstances. Summary: The NCAA ISP has a long-standing role in supplying NCAA stakeholders with crucial injury surveillance data, playing a critical part in safeguarding student-athletes participating in collegiate sports.